163k views
18 votes
Read the instructions

Read the instructions-example-1
User Oberon
by
5.0k points

1 Answer

11 votes

Answer:

Explanation:


(5x - 2)/(4)+(1)/(2)=(3y+2)/(2)

Multiply the equation by 4


4*(5x - 2)/(4)+4*(1)/(2)=4*(3y+2)/(2)\\

5x - 2 + 2 = 2*(3y + 2)

5x +0 = 2*3y + 2*2

5x = 6y + 4

5x - 6y = 4 --------------------(I)


(7y+3)/(3)=(x)/(2)+(7)/(3)\\

Multiply the equation by 6


6*(7y+3)/(3)=6*(x)/(2)+6*(7)/(3)\\

2*(7y + 3) = 3x + 2*7

14y + 6 = 3x + 14

14y = 3x + 14 - 6

14y = 3x + 8

-3x + 14y = 8 ------------------------(II)

Multiply equation (I) by 3 and equation (II) by 5 and then add

(I)*3 15x - 18y = 12

(II)*5 -15x + 70y = 40 {Now add}

52y = 52

y = 52/52

y = 1

Substitute y =1 in equation (I)

5x - 6*1 = 4

5x - 6 = 4

5x = 4 +6

5x = 10

x = 10/5

x = 2

User Etan
by
4.5k points